(untitled) (Coffee Science - ISSN 1984-3909, 2015)
We investigated the response from antioxidant system of Coffea arabica L. seedlings from Catuaí and Mundo Novo cultivars to waterlogging. For this, acclimated seedlings with eight pairs of completely expanded leaves were submitted to three conditions of water availability: field capacity, intermittent waterlogging and continuous waterlogging. The evaluations were performed at the beginning of the experiment and five months after waterlogging. Activity of antioxidant enzymes and levels of ascorbate were evaluated. There was a response of enzymatic and non-enzymatic antioxidant system of coffee seedlings to stress condition, allowing the plants to survive under waterlogging for 150 days. The antioxidant system was more active in Catuaí than in Mundo Novo cultivar.